PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI, LOKASI, KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN DI RUMAH MAKAN BEBEK KALEO TEBET JAKARTA SELATAN DIMASA PANDEMI COVID-19 - Aris Budiono (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
ABSTRACT This study analyzes the effect of product quality, price perception, promotion, location, service quality on consumer loyalty through customer satisfaction at Bebek Kaleo Restaurant, Tebet, South Jakarta during the Covid-19 pandemic.Data collection through surveys with 105 respondents incidentally in October 2020. Data analysis techniques through Path Analysis, The Simultaneous Influence of Product Quality, Price, Promotion, Location, and Service Quality on Customer Satisfaction as well as Consumer Loyalty, Product quality, price perception, promotion have no effect on consumer satisfaction, location, service quality has a significant effect on customer satisfaction. Product Quality, Location Service Quality has no effect on Consumer Loyalty, Promotion and Satisfaction has a significant effect on Consumer Loyalty, all independent variables can directly influence the consumer loyalty variable without intervening customer satisfaction.Keywords : Product Quality, Price Perception, Promotion, Location, Service Quality, Customer Satisfaction, Consumer Loyalty